Neutronic Design of Uranium-Plutonium Nitride Fuel-Based Gas-Cooled Fast Reactor (GFR) (Department of Physics, Faculty of Mathematics and Natural Sciences, 2018)
This study presents the calculation results of the cell, and core Gas-cooled Fast Reactor (GFR) based fuel Uranium-Plutonium Nitride (U, Pu)N. Parameter survey results of calculations of the fuel cell consisting of a kinf, burnup level, and the conversion ratio and for the calculation of the reactor core produce value keff during a refueling cycle. The calculation was performed by using a set of SRAC program by comparing three types of fuel cell designs. Reactor Design A based on natural uranium could not reach criticality because of keff 1. Design B used the enrichment of uranium-235 by 9.5% to reach a critical condition at keff 1. The critical state was also achieved by Design C utilizing natural uranium, and plutonium 5.5% result value keff = 1.015 in the first year of burnup and continues to increase 1.083 in the tenth year without refueling. Moreover, plutonium can replace the uranium enrichment process.Penelitian ini menyajikan hasil perhitungan sel dan teras gas-cooled fast reactor (GFR) berbasis bahan bakar Uranium- Plutonium Nitride (U,Pu)N. Parameter Survey untuk hasil perhitungan sel bahan bakar terdiri dari kinf, level burnup, dan conversion ratio. Sedangkan pada perhitungan teras reaktor dihasilkan nilai keff untuk satu siklus pengisian bahan bakar. Perhitungan dilakukan dengan menggunakan seperangkat program SRAC dengan membandingkan tiga jenis desain sel bahan bakar yang berbeda. Reaktor Desain A berbasis uranium alam tidak mencapai kekritisan karena keff 1. Desain B menggunakan pengayaan uranium-235 sebesar 9,5% mencapai kondisi kritis pada keff 1. Keadaan kritis juga dicapai oleh Desain C yang memanfaatkan uranium alam dan plutonium 5,5% menghasilkan nilai keff = 1,015 di tahun pertama burnup dan terus meningkat hingga 1,083 pada tahun kesepuluh tanpa pengisian ulang bahan bakar. Pemanfaatan plutonium sebagai bahan bakar dapat menggantikan proses pengayaan pada uranium.